2013
DOI: 10.1631/jzus.b1200317
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of hydrogen-rich saline on ischemia/reperfusion injury in rat skin flap

Abstract: Abstract:Objective: Skin damage induced by ischemia/reperfusion (I/R) is a multifactorial process that often occurs in plastic surgery. The mechanisms of I/R injury include hypoxia, inflammation, and oxidative damage. Hydrogen gas has been reported to alleviate cerebral I/R injury by acting as a free radical scavenger. Here, we assessed the protective effect of hydrogen-rich saline (HRS) on skin flap I/R injury. Methods: Abdominal skin flaps of rats were elevated and ischemia was induced for 3 h; subsequently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 30 publications
0
46
0
Order By: Relevance
“…After reperfusion, inflammatory cell infiltration in injured tissues is responsible for the production of inflammatory factors, including TNF-a and IL-6, which subsequently trigger a feedback loop in inflammatory cascades, leading to tissue dysfunction and damage (Aboutaleb et al, 2019). Moreover, inflammatory cytokines can further activate the immune/ inflammatory response and result in the extension of injury (Zhao et al, 2013). Consequently, cellular apoptosis and tissue necrosis are induced.…”
Section: Discussionmentioning
confidence: 99%
“…After reperfusion, inflammatory cell infiltration in injured tissues is responsible for the production of inflammatory factors, including TNF-a and IL-6, which subsequently trigger a feedback loop in inflammatory cascades, leading to tissue dysfunction and damage (Aboutaleb et al, 2019). Moreover, inflammatory cytokines can further activate the immune/ inflammatory response and result in the extension of injury (Zhao et al, 2013). Consequently, cellular apoptosis and tissue necrosis are induced.…”
Section: Discussionmentioning
confidence: 99%
“…Even in cases of microsurgical transfer by experienced hands in the presence of a stable blood supply, skin flap loss still ranges from 1% to 5%. 13,14 There are many reasons for partial or total flap loss, including I/R injury. I/R injury is tissue damage caused by the blood supply returning to the tissue after a period of ischemia; cell death is the worst consequence of ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…This study reveals Nec-1 may have therapeutic potential to prevent and treat I/R injury in flap transplantation. 13 By using Nec-1, we might partly protect flaps from I/R injury after surgery. Especially in patients with a high risk of flap complications (diabetes, malnutrition, and infection).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 In addition, hydroxyl radicals are mainly released at early phase after reperfusion. Zao et al 21 reported the protective effect of hydrogen-rich solution on the abdominal skin flap after ischemia reperfusion by intraperitoneal administration. Chuai et al 20 showed the reduction rate of hydroxyl radicals had strong correlation with hydrogen concentration.…”
Section: Discussionmentioning
confidence: 99%